ANALISIS PERKEMBANGAN KINERJA KEUANGAN PADA PT. PEGADAIAN (PERSERO) TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - AZA NURHIKMA; Mariam Makmur; Suriadi Suriadi (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2024)
There are various types of state-owned companies in Indonesia that are engaged in various fields, one of which is PT Pegadaian Persero tbk. Pegadaian is a company that aims to overcome people who are in need of money so as not to take loans to bonded dealers or commonly said to be loan sharks where they provide relatively high interest. The company's financial performance can be interpreted as a form of financial statement results that have been analyzed to determine the results of the company's performance and assess potential changes in resources owned during the specified period. The main objective of this study is to determine how the development of the company's performance of PT Pegadaian (Persero) tbk based on the results of the liquidity ratio, profitability ratio, activity ratio, and solvency ratio. The method used in this research is to use a quantitative approach with the data source used is secondary data and the data collection technique is based on documentation from the financial statements obtained and then analyzed using descriptive analysis using financial ratio analysis. The results of this study based on liquidity ratios, solvency, activity, and profitability show the company is in poor condition. Keywords: Financial Performance, Liquidity, Profitability, Activity, and Solvency Ratios